Biorate: a stress-responsive biophilic rating tool for Malaysian indoor office spaces - Abdul Munir, Fadhlizil Fariz; Sapian, Abdul Razak; Mansor, Mazlina; Shahbudin, Mohammad Syathir Amini; Ismail, Amirul Amin; Muhamad, Jamaludin (2025)
The integration of biophilic design in workplace environments is increasingly recognised for its ability to enhance well-being, reduce stress, and improve productivity. This study introduces a Biophilic Design Rating Tool specifically tailored for indoor office settings in Malaysia, developed through empirical validation that involved virtual reality (VR) simulations and biometric assessments. The tool comprises 34 attributes categorised under three dimensions: Natural Environment, Composition, and Personal Experience, each further divided into subcategories such as visual and non-visual elements, spatial qualities, and psychological stimuli. Attributes are scored and weighted to classify environments into four levels of restorative quality: Certified, Silver, Gold, and Platinum. Biometric data collection involved the use of heart rate variability (HRV) and skin conductance level (SCL) to evaluate emotional and stress responses during VR-based environmental exposure using Quest 3. A total of 50 government office workers in Putrajaya participated in the testing phase, experiencing a range of simulated office environments designed with varying levels of biophilic integration. Participants' physiological responses and preference feedback were used to refine the scoring structure and weightage distribution. Findings revealed a strong correlation between higher biophilic scores and reduced stress indicators, supporting the validity of the tool. The final product is delivered as an Excel-based application, providing a practical and user-friendly method for assessing the restorative potential in indoor office environments. Designed for commercial scalability, this tool is intended for designers, consultants, and policymakers, with the potential to support national initiatives such as MyCREST and GBI Malaysia through integration into building performance evaluation frameworks.